Examining the Relationships among Servant Leadership, Organizational Commitment, and Job Satisfaction within Government Organizations in Cambodia - Sarom Mok; Ramy Chhun; Mengheang Hor; Kosal Thay; Chamnan Sok (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Although servant leadership (SELE) has been understudied, especially in the public sector, it has been a popular topic in contemporary leadership theories and has been linked to outcomes like job satisfaction (JOSA) and organizational commitment (ORCO). Given its importance, this study was to ascertain if official JOSA and ORCO were predicted by government official perceptions of SELE, and whether ORCO moderated the relationship between SELE and JOSA. This study used a correlational research design. A structured questionnaire was used to gather data from 224 government officials from various departments both in leadership and non-leadership roles. The Servant Leadership Seven, the Organizational Commitment Questionnaire, and the Abridged Job Descriptive Index were among the online surveys used to gather data for the study. Multiple regression to examine moderation effects, an independent-samples t-test, and Pearson correlations were among the statistical methods used. The findings showed a correlation between higher levels of ORCO and JOSA among government officials and higher perceptions of SELE. There was a significant positive correlation found between department leader JOSA, top management, and SELE, indicating that SELE is linked to government official attitudes at several organizational levels. The results also revealed that managerial self-ratings of SELE differed significantly from non-managerial ratings, with leaders giving their leadership behaviors higher ratings than officials. While organizational commitment and servant leadership both strongly predicted job satisfaction, the moderation analysis revealed that ORCO did not moderate the connection between SELE and JOSA. The findings imply that staff morale and institutional loyalty are positively impacted by SELE. The results emphasize how crucial SELE is in influencing official attitudes in government organization settings and imply that its beneficial effects hold true for all government official roles.